Lactic Acid Bacteria Diversity in Fermented Foods as Potential Bio-Resources Contributing to Alleviate Malnutrition in Developing Countries: Nigeria as a Case Study - Elizabeth T. Adesemoye; Abiodun I. Sanni; Giuseppe Spano; Vittorio Capozzi; Mariagiovanna Fragasso (Fermentation)
Fermented products represent ecological niches for developing microorganisms of interest as bio-resources for improving human well-being. Lactic acid bacteria (LAB) are frequently associated with food fermentations and represent relevant biotechnological resources for enhancing the overall quality of foods and beverages. Among the other potential applications, LAB isolated from traditional fermented foods can play a significant role in addressing malnutrition in developing countries, positively modulating the finished products’ nutritional quality. Nigeria represents an excellent model region to explore this topic as (i) it is a country where the magnitude of phenomena associated with malnutrition is high; (ii) there is a significant effort linked to the achievement of Sustainable Development Goals (SDGs) of the Food and Agriculture Organization (FAO) of the United Nations (UN); and (iii) there is an interesting diversity of traditional fermented foods and beverages. In nations such as Nigeria, fermented foods are integral to infant and young child nutrition, often serving as complementary foods. This review proposes a detailed overview of traditional Nigerian fermented products, including ogi, gari, fufu, lafun, kunu-zaki, masa, wara, kobele, abacha, pito, and burukutu. An overview of the microbial diversity associated with these matrices is also provided, considering a specific focus on LAB responsible for the spontaneous fermentation of various Nigerian foods. We underlined the potential of different LAB species/stains to produce vitamins naturally, particularly B-group vitamins, suggesting strategies that can be followed for in situ biofortification, enhancing the nutritional value of fermented products. In general, the review, summarizing data on microbial diversity presented in principal traditional fermented foods and beverages in Nigeria, supports future studies to exploit the potential of LAB species/strains from fermented foods to combat micronutrient deficiencies in developing countries, such as Nigeria, with the objective to mitigate hidden hunger and alleviate malnutrition in vulnerable populations.